B-1a Cell Development in Splenectomized Neonatal Mice - Pedersen, Gabriel K.; Li, Xiaohong; Khoenkhoen, Sharesta; Ádori, Monika; Beutler, Bruce; Karlsson Hedestam, Gunilla B. (Frontiers in Immunology, 2018)
B-1a cells are mainly generated from fetal liver progenitor cells, peri- and neonatally. The developmental steps and anatomical sites required for these cells to become mature B-1a cells remain elusive. We recently described a phenotypically distinct transitional B cell subset in the spleen of neonatal mice that generated B-1a cells when adoptively transferred. This, in combination with findings demonstrating that B-1a cells are lacking in congenitally asplenic mice, led us to hypothesize that the neonatal spleen is required for B-1a cell development. In accordance with previous reports, we found that B-1a cell numbers were reduced in adult mice that had undergone splenectomy compared to after sham surgery. In contrast, neonatal splenectomy led to peritoneal B-1a cell frequencies comparable to those observed in sham-operated mice until 6 weeks after surgery, suggesting that an intact spleen is required for B-1a cell maintenance rather than development. To study the role of the prenatal spleen in generating B-1a cells, we transferred fetal liver cells from pre-splenic embryos (embryonic age 11 (E11) days) into splenectomized recipient mice. B-1a cells were generated in the absence of the spleen, albeit at slightly reduced frequencies, and populated the peritoneal cavity and bone marrow. Lower bone marrow B-1a cell frequencies were also observed both after neonatal and adult splenectomy. These results demonstrated that B-1a cells could be generated in the complete absence of an intact spleen, but that asplenia led to a decline in these cells, suggesting a role of the spleen for maintaining the B-1a compartment.